Evans Blue Inhibits HBV Replication Through a Dual Antiviral Mechanism by Targeting Virus Binding and Capsid Assembly - Xiao, Yu; Liu, Chunlan; Tang, Wei; Zhang, Haiwei; Chen, Xulin (Frontiers in Microbiology, 2019)
Chronic hepatitis B (CHB) is a global health problem caused by the human hepatitis B virus (HBV). Current treatment with interferons and nucleos(t)ide analogs (NAs) can cause population tolerance and drug resistance. Therefore, new antiviral drugs, especially those targeting host factors, are urgently needed. Here, we identified Evans blue as a new HBV inhibitor by screening an FDA drug library using Huh7DhNTCP cells and confirmed the antiviral activity in primary human hepatocytes and human sodium taurocholate cotransporting polypeptide (hNTCP)-transfected porcine primary hepatocytes (PPH). Our efficacy study showed that Evans blue has an IC50 of 2 μM against HBV infection in Huh7DhNTCP cells, and no apparent toxicity at up to 1000 μM. The IC50 of Evans blue against HBV in primary human hepatocytes was approximately five μM. Mechanism studies revealed that Evans blue has a dual anti-HBV effect. It inhibits both the binding of viral preS1 to host cells through the host factor NTCP and the virus capsid assembly by targeting the host factor BK channel. The KD of the direct interaction between Evans blue and NTCP is 8.82E-8 M. Evans blue can suppress capsid assembly at micromolar concentrations by reducing the cytosolic calcium ion concentration. Since the antiviral effects on HBV binding and assembly are both achieved through targeting host factors, Evans blue inhibits the infection of nucleos(t)ide analog drug-resistant HBV strains in Huh7DhNTCP cells. Taken together, our results suggest that Evans blue may be a promising anti-HBV drug candidate in the classes of both entry and assembly inhibitors.